ANALISA PENGGANTIAN KWH METER BERMASALAH TERHADAP EFEKTIFITAS KWH JUAL - Nuralda, Dewi Victorya (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. kWh Meter is a tool used to measure and record the use of electrical energy consumed by customers. However, there are still problematic that occur in the kWh meter caused by several factors such as jammed kWh, blurry kWh and old kWh. This problematic affects the measurement of electrical energy in the kWh meter installed on the customer. The average use of the kWh before being replaced with the average usage after being replaced shows an increase. This shows that there is an anomaly in the changed kWh meter. This Final Report will discuss this matter. The methodology used in this Final Report is the literature method, the observation method, as well as the consultation and discussion method. The author collects data by seeking information from books, articles, internet, and journals related to titles that can support the progress of this final report. The author also made direct observations on objects in the field located in the PT. PLN (Persero) ULP Muara Enim. Then the author conducted discussions with supervisors and PLN staff. The conclusion that can be drawn from this Final Report is that there is an increase in the value of kWh after replacing the problematic kWh meter, which previously the average usage was only 3,282 kWh then after replacing the average usage increased to 4,011 kWh, so there is a difference in the average usage of 729 kWh. The replacement of jammed and blurry kWh meters increases the effectiveness of selling kWh by 22.21%. So there is difference in costs which is a loss that in charge of PT. PLN of Rp. 904.328/month.